Numerical analysis for the influence of the geometrical and mechanical parameters on the stiffness and strength of the composite bolted joints - Calin-Dumitru COMAN (INCAS Bulletin, 2018)
The paper deals with the influence of the geometric (joint clearance) and mechanical parameters (bolt preload, axial force applied to the joint) on the stiffness and strength of the single-bolt, single-shear laminated composite joints using epoxy resin and carbon fibers reinforcement. In the first part of the paper, the finite element model is presented, using three-dimensional elements for studding the influence of the geometric and mechanical parameters on the stiffness of the joint. In the second part, the microscopic failure of the constituent layers using the Hashin failure criterion for composite materials is presented, as well as the influence of the studied parameters on the occurrence of the first lamina failure and the progressive failure phenomenon from the microscopic to the macroscopic level of the joint.